Characterization of Natural Killer Cells in Tamarins: A Technical Basis for Studies of Innate Immunity - Yoshida, Tomoyuki; Saito, Akatsuki; Iwasaki, Yuki; Iijima, Sayuki; Kurosawa, Terue; Katakai, Yuko; Yasutomi, Yasuhiro; Reimann, Keith A.; Hayakawa, Toshiyuki; Akari, Hirofumi (Frontiers in Microbiology, 2010)
Natural killer (NK) cells are capable of regulating viral infection without major histocompatibility complex restriction. Hepatitis C is caused by chronic infection with hepatitis C virus (HCV), and impaired activity of NK cells may contribute to the control of the disease progression, although the involvement of NK cells in vivo remains to be proven. GB virus B (GBV-B), which is genetically most closely related to HCV, induces acute and chronic hepatitis upon experimental infection of tamarins. This non-human primate model seems likely to be useful for unveiling the roles of NK cells in vivo. Here we characterized the biological phenotypes of NK cells in tamarins and found that depletion of the CD16+ subset in vivo by administration of a monoclonal antibody significantly reduced the number and activity of natural killer cells.